2021
DOI: 10.3389/fpls.2021.707256
|View full text |Cite
|
Sign up to set email alerts
|

Plant Endophytic Fungus Extract ZNC Improved Potato Immunity, Yield, and Quality

Abstract: Endophytic fungi play an important role in plant survival and reproduction, but the role of their metabolites in plant growth and immunity, as well as in crop quality formation, is poorly understood. Zhinengcong (ZNC) is a crude ethanol extract from the endophytic fungus Paecilomyces variotii, and previous studies have shown that it can improve the growth and immunity in Arabidopsis thaliana. The aim of the study was to reveal the trade-off balance between plant growth and immunity by evaluating the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…According to recent research findings, ZNC can stimulate PTI through the FLG22 and chitin signaling pathways to enhance plant disease resistance, enhance the expression of IAA and N absorption-related genes, and improve plant metabolism to promote plant growth. 32 When DAP compounded coating ZNC, it was able to keep ZNC alive, limit the release of ZNC and nutrients together, promote the growth and development of crops, and further improve maize yield and PUE. However, the results of this study showed that ZNC combined with CDAP had a better yield-increasing effect in 2017 than the treatments CDAP or DAP combined with ZNC, increasing maize yield by 9.6 and 14.3%, respectively, and the yield difference was not significant in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent research findings, ZNC can stimulate PTI through the FLG22 and chitin signaling pathways to enhance plant disease resistance, enhance the expression of IAA and N absorption-related genes, and improve plant metabolism to promote plant growth. 32 When DAP compounded coating ZNC, it was able to keep ZNC alive, limit the release of ZNC and nutrients together, promote the growth and development of crops, and further improve maize yield and PUE. However, the results of this study showed that ZNC combined with CDAP had a better yield-increasing effect in 2017 than the treatments CDAP or DAP combined with ZNC, increasing maize yield by 9.6 and 14.3%, respectively, and the yield difference was not significant in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research findings, ZNC can stimulate PTI through the FLG22 and chitin signaling pathways to enhance plant disease resistance, enhance the expression of IAA and N absorption-related genes, and improve plant metabolism to promote plant growth . When DAP compounded coating ZNC, it was able to keep ZNC alive, limit the release of ZNC and nutrients together, promote the growth and development of crops, and further improve maize yield and PUE.…”
Section: Discussionmentioning
confidence: 99%
“…As a chemical fertilizer, ZNC promotes plant growth and defense against pathogens at a very low dosage (Yan et al, 2020). According to previous studies in the role of ZNC in stress resistance and growth, ZNC performs best in root growth of Arabidopsis at 1-100 ng/ml, bacterial resistance of Arabidopsis at 10-100 ng/ml, virus resistance of tobacco at 100-150 ng/ml, plants growth and oomycete resistance of potato at 1-100 ng/ml, which indicate that ZNC has high activity (Lu et al, 2019;Yan et al, 2020;Cao et al, 2021). Consistently, in our study, 20 ng/ml ZNC could effectively alleviate heat stress-induced inhibition on pollen grains and increase the production of tomato fruits and seeds (Figures 2,4,5).…”
Section: Discussionmentioning
confidence: 91%
“…Zhinengcong (ZNC), a crude extract from the endophytic fungus Paecilomyces variotii , is able to improve plant growth and resistance to biotic and abiotic stresses. ZNC was found to promote the growth and immunity of Arabidopsis thaliana ( Lu et al, 2019 ), potato yield, quality and resistance to Phytophthora infestans indoors and in the field ( Cao et al, 2021 ). ZNC was also found to enhance tobacco resistance to potato X virus by promoting RNA silencing and the SA pathway ( Peng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that ZhiNengCong (ZNC), an extract of the endophyte Paecilomyces variotii , can protect plants against pathogenic infection ( Lu et al, 2019 ; Cao et al, 2021 ). To investigate the effective immune fraction of ZNC, high-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC–MS) were performed.…”
Section: Resultsmentioning
confidence: 99%